Legal Analysis of the Application of Criminal Elements in Land Acquisition for Development Interest General - Suyadi, Yagus; Hutomo, Putra (Journal Evidence Of Law, 2025)
The definition of land acquisition is essentially a legal act in the form of releasing land rights from the entitled party before the competent authority by receiving compensation. In the issue of land supply by the state is very necessary in the implementation of national development and it can be ascertained that the availability of land for development activities becomes its own problem related to land prices, land status and acquisition mechanisms as well as criminal problems arising from land acquisition. However, in its implementation, we often find irregularities that occur, both in the collection of physical data and juridical data, there can also be elements of inaccuracy and abuse of authority which leads to the imposition of elements of criminal acts. The arrangement of laws and regulations has been such that in its implementation it does not cause legal problems starting from the planning stage, as well as in its implementation, for this reason, socialization of land acquisition legal arrangements to land acquisition implementers, entitled parties and all parties involved is the key to success in land acquisition activities.